Perlindungan Hukum bagi Anak sebagai Korban Kekerasan dalam Rumah Tangga - Amrullah Amrullah; Fauziah Fauziah; Muhammad Sadri (Legal Note, 2025)
Children are individuals who are still in the stages of physical and mental development, and therefore require special protection, especially when they become victims of domestic violence (DV). Violence against children within the family can occur in the form of physical, psychological, sexual abuse, or neglect. Legal protection is crucial to guarantee children's rights and to prevent long-term adverse effects on their growth and development. In the context of national law, child protection is regulated by various legislations such as Law No. 23 of 2002 on Child Protection and Law No. 23 of 2004 on the Elimination of Domestic Violence. Furthermore, Indonesia has ratified the Convention on the Rights of the Child as a commitment to the global protection of children's rights. This study employs a normative juridical approach by examining relevant legal regulations and literature. The main focus of this study is to identify the forms of legal protection provided to children as victims of domestic violence and to evaluate the effectiveness of its implementation in practice. The results of the study show that, normatively, legislation has provided a strong legal foundation for child protection. However, its implementation in the field still faces various challenges. For instance, law enforcement officers do not fully understand the principle of the best interest of the child, rehabilitation and counseling services remain limited, and the persistence of patriarchal culture causes victims to be reluctant to report. Therefore, strong synergy is needed between the government, child protection institutions, law enforcement, and the community in an effort to provide comprehensive and effective legal protection. It is also necessary to enhance the capacity of human resources in protection agencies, provide child-friendly facilities, and conduct legal education and public awareness campaigns. With a comprehensive approach, it is expected that children who are victims of domestic violence will receive protection, recovery, and justice in accordance with their constitutional rights and universal humanitarian values.